PROTECTION OF INFORMATION IN THE CYBERSECURITY SYSTEM AS A STRATEGIC IMPLEMENTATION PRIORITY FOR STATE MECHANISMS OF NATIONAL VALUES PROTECTION IN UKRAINE - Stanislav Larin (Публічне управління та регіональний розвиток)
The article analyses the research of information security threats in the cybersecurity system, which the author considers a strategic implementation priority for state mechanisms of national values protection in Ukraine.